Effect of Aluminum Powder on Underwater Explosion Performance of CL‐20 Based Explosives. Issue 7 (23rd May 2019) - Hu, Hongwei; Chen, Lang; Yan, Jiajia; Feng, Haiyun; Xiao, Chuan; Song, Pu
Abstract: The influences of particle size distributions of the nano and micro‐aluminum powders on the underwater explosion were analyzed experimentally. Both shock waves and the second pressure pulses induced by the CL‐20 based explosives were measured. Furthermore, the shock wave energy, the bubble energy, the reacting quantity of aluminum powders in the CL‐20 based explosives during the detonation and secondary reaction processes were calculated. The results indicate that: the nano‐aluminum powders have significant influences on both the detonation reaction and the secondary reaction, leading to the higher peak pressure of the shock wave while the lower peak pressure and narrower pulse width of the secondary pressure pulse; the gradations of both nano and micro‐aluminum powders improve the energy outputs of the explosives; the nano‐aluminum powders enhance the shock wave pressure while the micro‐aluminum powders maintain higher bubble energy. Abstract :